Firm-Specific Capital and Welfare - Tommy Sveen; Lutz Weinke (Norges Bank, 2006)
What are the consequences for monetary policy design implied by the fact that price setting and investment takes typically place simultaneously at the firm level? To address this question we analyze simple (constrained) optimal interest rate rules in the context of a dynamic New Keynesian model featuring firm-specific capital accumulation as well as sticky prices and wages al̀a Calvo. We make the case for Taylor type rules. They are remarkably robust in the sense that their welfare implications do not appear to hinge neither on the specific assumptions regarding capital accumulation that are used in their derivation nor on the particular definition of natural output that is used to construct the output gap. On the other hand we find that rules prescribing that the central bank does not react to any measure of real economic activity are not robust in that sense.
hdl:11250/2498374
Keywords: E22; E31; E52; 330; monetary policy; sticky prices; aggregate investment